2007
DOI: 10.1111/j.1365-2958.2007.05896.x
|View full text |Cite
|
Sign up to set email alerts
|

Spore cortex formation in Bacillus subtilis is regulated by accumulation of peptidoglycan precursors under the control of sigma K

Abstract: SummaryThe bacterial endospore cortex peptidoglycan is synthesized between the double membranes of the developing forespore and is required for attainment of spore dehydration and dormancy. The Bacillus subtilis spoVB, spoVD and spoVE gene products are expressed in the mother cell compartment early during sporulation and play roles in cortex synthesis. Here we show that mutations in these genes block synthesis of cortex peptidoglycan and cause accumulation of peptidoglycan precursors, indicating a defect at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 63 publications
7
57
0
Order By: Relevance
“…Thus, SpoVE localizes in a pattern that closely matches the membrane dynamics of the engulfing forespores. Further, the pattern at later time points (post-3 h) is consistent with the role of SpoVE in spore cortex synthesis, a late (postengulfment) event in sporulation (50). The examination of SpoVE-YFP expression by immunoblotting analysis of samples taken at equivalent time points demonstrated that the protein appeared at 3 h, consistent with the results of microscopy (data not shown).…”
Section: Localization Of Spovesupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, SpoVE localizes in a pattern that closely matches the membrane dynamics of the engulfing forespores. Further, the pattern at later time points (post-3 h) is consistent with the role of SpoVE in spore cortex synthesis, a late (postengulfment) event in sporulation (50). The examination of SpoVE-YFP expression by immunoblotting analysis of samples taken at equivalent time points demonstrated that the protein appeared at 3 h, consistent with the results of microscopy (data not shown).…”
Section: Localization Of Spovesupporting
confidence: 75%
“…spoVE, which during sporulation is expressed under the control of the mother cell-specific transcription factor E (45), is not essential for vegetative growth, yet it is absolutely required for the production of cortex PG. Thus, during sporulation, ⌬spoVE mutants fail to form a cortex (15,34,50) and they accumulate cytoplasmic PG precursors (50), suggesting a defect at an early step in PG polymerization and consistent with the view that the SEDS proteins may function in lipid-linked precursor translocation. SpoVE may be part of a third putative PG biosynthetic complex of B. subtilis and other endospore-forming bacteria which includes a sporulation-specific, E -controlled PBP, called SpoVD, required for synthesis of the cortex (4).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…1; Table 2). Consistent with the proposed role of MviN as the lipid II flippase, strains lacking SpoVB are defective in the synthesis of spore cortex peptidoglycan and accumulate peptidoglycan precursors (32).…”
Section: Resultsmentioning
confidence: 70%
“…These proteins have also been shown to mediate resistance to a wide range of cationic dyes, fluoroquinolones, aminoglycosides, and other structurally diverse antibodies and drugs (15). MATE proteins have also been implicated in the production of polysaccharides, such as RfbX (Wzx) (4) and WzxE (17), which have been implicated in E. coli Oantigen biosynthesis; Bacillus subtilis SpoVB, which is involved in spore cortex biosynthesis (16,19); and eukaryotic RFT1, which is required for translocation of the dolichyl diphosphateMan 5 GlcNAc 2 intermediate, an oligosaccharide complex used in protein glycosylation, from the cytosolic side of the endoplasmic reticulum membrane to the lumen during the biosynthesis of dolichyl diphosphate-Glc 3 Man 9 GlcNAc 2 (8). These results suggest that MviN may be involved in the transmembrane transport of peptidoglycan precursors across the inner membrane.…”
mentioning
confidence: 99%